A PRELIMINARY STUDY OF ENGLISH LANGUAGE LEARNING INITIATION AT RA’IYATUL HUSNAN ISLAMIC BOARDING SCHOOL - Muhammad Nawawi Ivan; Feri Ferdiyanto (J-Shelves of Indragiri (JSI), 2026)
This preliminary study aims to initiate English language learning at Ra’iyatul Husnan Islamic Boarding School, where no internal English learning activities had previously been implemented. Although students received English instruction in formal schools, their practical language ability remained limited due to the lack of continuous practice and learning support within the pesantren environment. This study employed a qualitative approach using the Asset-Based Community Development (ABCD) framework. Data were collected through observation, interviews, and documentation involving approximately 60 first- and second-grade Islamic junior high school students. Initial findings revealed that 65% of students were unfamiliar with the English alphabet and 80% were unable to construct simple English sentences. The learning program focused on basic materials such as alphabets, daily vocabulary, introductions, numbers, and simple sentence structures. After fifteen days of implementation, more than 70% of students were able to introduce themselves, mention numbers, tell time, and use basic personal pronouns in English. The findings also indicate increased student motivation and participation in collaborative learning activities. The study concludes that the ABCD approach effectively supports the initiation of English language learning in pesantren by utilizing existing institutional and social assets to create sustainable learning practices.